Effects of future sea level rise on coastal habitat. Issue 3 (3rd February 2019) - Von Holle, Betsy; Irish, Jennifer L.; Spivy, Annette; Weishampel, John F.; Meylan, Anne; Godfrey, Matthew H.; Dodd, Mark; Schweitzer, Sara H.; Keyes, Tim; Sanders, Felicia; Chaplin, Melissa K.; Taylor, Nick R.
ABSTRACT: Sea level rise (SLR) and disturbances from increased storm activity are expected to diminish coastal ecosystems available to nesting species by removing habitat and inundating nests during incubation. We updated the United States Geological Survey's (USGS) Coastal Vulnerability Index, which provides a qualitative and relative assessment of a coastal area's vulnerability to erosion and shoreline retreat as a function of SLR and other factors, for the South Atlantic Bight. We considered a eustatic SLR projection of 14 cm by 2030. We linked long‐term survey data for 3 sea turtle species, 3 shorebird species, and 5 seabird species to future coastal erosion vulnerability to SLR to understand effects of future SLR on nesting habitats. Over 2, 000 km (43%) of the South Atlantic Bight coastline is projected to have an increase in coastal erosion vulnerability by the 2030s, with respect to its present vulnerability. Future vulnerability of SLR‐induced erosion along the South Atlantic Bight is spatially variable, and the 11 coastal study species also varied in their use of coastal habitats with high future coastal vulnerability to SLR. For example, only 23% of high‐density nesting habitat for the brown pelican ( Pelecanus occidentalis ) is expected to be at increased vulnerability to SLR, whereas >70% of the high‐nesting density habitat for 2 seabird species (gull‐billed tern [ Gelochelidon nilotica ], sandwich tern [ Thalasseus sandvicensis ]) is predicted to have higher future coastal erosion vulnerability by 2030. We provide predictions for the level of susceptibility of the study species to erosion from future SLR, which is the first step in managing coastal species for the changing environmental conditions associated with climate change and SLR. © 2019 The Authors. Journal of Wildlife Management Published by Wiley Periodicals, Inc. on behalf of The Wildlife Society. Abstract : Erosion from future sea level rise varies along the South Atlantic Bight, and the degree of use of vulnerable habitats varies among 11 coastal study species. Conservation managers can use our broad‐scale approach to align high nesting density habitats with those areas predicted to have high future coastal vulnerability.